Research on the Role of Marriage Status Among Women Underwent Breast Reconstruction Following Mastectomy: A Competing Risk Analysis Model Based on the SEER Database, 1998–2015 - Zhang, Siyuan; Yang, Zejian; Qiu, Pei; Li, Juan; Zhou, Can (Frontiers in Surgery, 2022)
Background: Marital status is an important foundation of social public relations in modern society, but little is known about the role of marriage status among women undergoing breast reconstruction following mastectomy. This research mainly aimed to investigate the prognostic value of marital status in breast cancer women undergoing breast reconstruction. Methods: The demographic and clinical data of patients were obtained from Surveillance, Epidemiology, and End Results (SEER) Program database. Eligible population were assessed on overall survival (OS), breast cancer-specific survival (BCSS),and breast cancer-specific death (BCSD) through propensity score matching (PSM) method, multivariate Cox proportional hazards model analysis, competing risk model analysis, multivariate competing risk regression model analysis, and subgroup analysis. Results: Of the 54683 women included in the current study, a total of 38110 participants were married patients (married group), and 16573 participants were unmarried patients (unmarried group). Patients in the married group tended to have better OS (HR=1.397, 95% CI: 1.319-1.479, P<0.001), BCSS (HR=1.332, 95% CI: 1.244-1.426, P<0.001), cumulative BCSD incidence (Gray’s test, P<0.001) and OCSD incidence (Gray’s test, P<0.001) than those in the unmarried group. In subgroup analysis, subjects with HR+/HER2- subtype breast cancer in the married group showed improved OS (OS: 1.589, 95% CI: 1.363-1.854, P<0.001) and BCSS (BCSS: HR=1.512, 95% CI: 1.255-1.82, P<0.001) than those in the unmarried group. Conclusions: Our study demonstrated that the inexistence of marriage was associated with poorer OS and BCSS, especially for HR+/HER2- breast cancer women undergoing breast reconstruction.